Electrolyte and lithium ion battery
By adding specific additives to the electrolyte of lithium-ion batteries, the problem of SEI film instability during the circulation of silicon-based materials is solved, and the rate performance, cycle performance and safety performance of lithium batteries are improved.
Patent Information
- Application Number
- CN202411920063.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The volume expansion of silicon-based materials during the circulation of lithium-ion batteries causes unstable SEI film, affecting rate performance and cycle stability, and may cause safety accidents.
An electrolyte is adopted to promote the dissociation and migration of lithium ions, enhance the stability of the SEI film, and improve the film formation stability of the electrode surface and the flame retardant effect of the electrolyte by adding 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxobolpentan-2-yl)pyridine and fluorine-containing sulfonate additives to the electrolyte.
It improves the rate performance, cycle performance and safety performance of lithium batteries, reduces the dissolution and rupture of SEI film, and enhances the stability and safety of the battery.
Smart Images

Figure BDA0005207918940000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to an electrolyte and a lithium-ion battery. Background Art
[0002] The main components of lithium-ion batteries include positive electrode sheets, negative electrode sheets, separators and electrolytes. Among them, the electrolyte is an important component of lithium-ion batteries. During the first charge and discharge process of lithium-ion batteries, the electrolyte reacts with the silicon-based material at the solid-liquid interface to form a passivation layer SEI film at the negative electrode interface. Lithium ions can be freely embedded and removed through the SEI film to achieve battery charging and discharging. Although traditional lithium-ion batteries have been widely used in portable electronic devices and electric vehicles, their energy density is limited and cannot meet higher application scenarios. Therefore, the research and development of high-energy-density lithium batteries has become an important topic at present.
[0003] Anode materials with high specific capacity are an important breakthrough in improving the energy density of lithium-ion batteries. Silicon-based materials are considered to be the most likely anode materials to replace graphite because of their high theoretical specific capacity, suitable discharge potential, and relatively abundant reserves in nature. However, there are many problems in the commercial application of silicon-based materials in lithium-ion batteries. Silicon-based materials are accompanied by a large volume expansion during the cycle. The volume change makes it impossible to form a stable SEI film on the surface of the anode using silicon-based materials. The SEI film repeatedly breaks and forms, consuming a large amount of lithium ions. The SEI film at the interface of the silicon-containing anode repeatedly grows and breaks, greatly affecting the rate performance and cycle stability of the lithium battery. In serious cases, the broken SEI film may cause a more violent reaction between the electrolyte and the electrode material, generating heat and gas, increasing the internal pressure of the battery, and possibly causing safety accidents.
[0004] Therefore, it is of great significance to develop an electrolyte for lithium batteries suitable for silicon-containing negative electrode systems to inhibit the destruction of the SEI film of silicon-based materials during the charge and discharge cycle of lithium batteries. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present application provides an electrolyte and a lithium ion battery.
[0006] In a first aspect, the present application provides an electrolyte, which adopts the following technical solution:
[0007] An electrolyte includes a first additive and a second additive, wherein the first additive includes 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine, and the second additive includes a fluorinated sulfonate additive.
[0008] The present application uses a first additive and a second additive in combination. The electron-deficient boron atom in the first additive can capture anions. Therefore, it can act as an anion receptor to coordinate with anions in the electrolyte, thereby promoting the dissociation of lithium ions and increasing the migration rate of lithium ions. The increase in free lithium content can reduce the dissolution of the SEI film, and the dioxaborolanyl group can absorb HF in the electrolyte, which helps to enhance the stability of the SEI film, thereby improving the rate performance and cycle performance of the lithium battery; the presence of the fluorine element in the second additive can react with the free lithium ions in the electrolyte, thereby promoting the formation of LiF interface film and Li2S interface film at the negative electrode, thereby improving the stability of the negative electrode SEI film, and the high ionic conductivity of LiF and Li2S helps to improve the rate performance of the lithium ion battery; further, the boron element in the first additive can cooperate with the sulfonic acid group in the second additive to improve the film formation stability on the electrode surface, and the combination of the fluorine element and the sulfonic acid group can improve the flame retardant effect of the electrolyte, which helps to further improve the fast charging safety of the lithium battery.
[0009] Preferably, the fluorinated sulfonate additive includes at least one of 2,2,3,3,3-pentafluoropropyl trifluoromethanesulfonate, 2,2,3,3-tetrafluoropropyl trifluoromethanesulfonate, 2,2-difluoroethyl trifluoromethanesulfonate, and hexafluoroisopropyl trifluoromethanesulfonate.
[0010] Preferably, the mass proportion of the first additive in the electrolyte is 1%-3%, and / or the mass proportion of the second additive in the electrolyte is 0.5%-2.5%.
[0011] By controlling the proportion of the first additive and the second additive in the electrolyte, on the one hand, while the first additive increases the amount of free lithium in the electrolyte, the addition of the second additive can react with the free lithium to form a LiF film, thereby avoiding the situation where the free lithium content in the electrolyte is too high due to the excessive content of the first additive. Excessive free lithium content will lead to a decrease in the ionic conductivity of the electrolyte, reduce the stability of the electrolyte during the charge and discharge cycle, and cause the electrolyte to decompose and produce gas, which is not conducive to improving the rate performance, cycle performance and safety performance of the lithium battery.
[0012] Preferably, it further comprises an organic solvent, a lithium salt, a lithium salt additive and a third additive.
[0013] Preferably, the third additive includes at least one of 1,3-propane sultone PS, vinyl sulfate DTD, and 1,3-propylene sultone PST;
[0014] The mass proportion of the third additive in the electrolyte is 1%-3%.
[0015] By introducing a third additive into the electrolyte and controlling the proportion of the third additive, on the one hand, the third additive can further improve the stability of the electrolyte, thereby cooperating with the first additive to improve the stability of the electrode / electrolyte interface; on the other hand, the third additive can form a sulfur-containing interface film at the negative electrode, which helps to improve the high-temperature cycle performance of the lithium battery.
[0016] Preferably, the lithium salt comprises lithium hexafluorophosphate LiPF6.
[0017] Preferably, the concentration of the lithium salt is 1-1.5 mol / L.
[0018] Preferably, the lithium salt additive includes at least one of lithium bis(fluorosulfonyl)imide salt LiFSI, lithium tetrafluoroborate LiBF4, lithium difluorophosphate LiPO2F2 and lithium bis(trifluoromethanesulfonyl)imide LiTFSI; the mass proportion of the lithium salt additive in the electrolyte is 0.1%-1%.
[0019] Preferably, the organic solvent includes at least one of a linear carbonate and a cyclic carbonate.
[0020] Preferably, the linear carbonate includes at least one of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC and methyl propyl carbonate MPC; the cyclic carbonate includes at least one of ethylene carbonate EC, fluoroethylene carbonate FEC and propylene carbonate PC.
[0021] Preferably, the mass ratio of the linear carbonate to the cyclic carbonate is 60-80:20-40.
[0022] By using linear carbonates and cyclic carbonates as solvents, it helps to adjust the electrolyte to an appropriate viscosity, thereby generating a stable SEI film on the surface of the negative electrode active material, and can improve the ionic conductivity and chemical stability of the electrolyte, thereby helping the first additive and the second additive to play a long-term coordinated role in the electrolyte, and further helping to improve the rate performance, cycle performance and safety performance of the lithium battery.
[0023] In a second aspect, the present application provides a lithium-ion battery, which adopts the following technical solution:
[0024] A lithium ion battery comprises a positive electrode sheet, a separator, a negative electrode sheet and the electrolyte as described above. DETAILED DESCRIPTION
[0025] For better understanding and implementation, the technical solution of the present application will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0027] Unless otherwise indicated, all numerical values expressing quantities of ingredients, reaction conditions, and so forth used in the specification and claims are to be understood as modified by the term “about.” Accordingly, unless indicated to the contrary, the numerical parameters set forth herein are approximations that can vary depending upon the desired properties desired to be obtained.
[0028] As used herein, "and / or" means one or all of the mentioned elements.
[0029] As used herein, “including” and “comprising” encompasses the case where only the stated elements are present as well as the case where there are other elements other than the stated elements.
[0030] All percentages in this application are by weight unless otherwise stated.
[0031] Unless otherwise indicated, "a", "an", "an" and "the" used in this specification are intended to include "at least one" or "one or more". For example, "a component" means one or more components, so more than one component may be considered and may be employed or used in the implementation of the embodiment.
[0032] The CAS number of the first additive 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine used in the present application is 1333222-12-0.
[0033] Example 1
[0034] 1. Preparation of Electrolyte
[0035] The mass proportion of the first additive in the electrolyte is 2%, the mass proportion of the second additive is 1.5%, the mass ratio of the linear carbonate to the cyclic carbonate in the organic solvent is 70:30, and the lithium salt concentration is 1.2 mol / L.
[0036] The first additive is 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine, and the second additive is 2,2,3,3,3-pentafluorotrifluoromethanesulfonic acid propyl ester;
[0037] The lithium salt is lithium hexafluorophosphate LiPF6;
[0038] The linear carbonates are dimethyl carbonate DMC and ethyl methyl carbonate EMC, and the cyclic carbonates are fluoroethylene carbonate FEC and propylene carbonate PC (DMC:EMC:FEC:PC=20:50:10:20);
[0039] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0040] 2. Preparation of positive electrode
[0041] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.
[0042] 3. Preparation of negative electrode sheet
[0043] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0044] 4. Selection of isolation film
[0045] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0046] 5. Preparation of Lithium-ion Batteries
[0047] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0048] Example 2
[0049] 1. Preparation of Electrolyte
[0050] The mass proportion of the first additive in the electrolyte is 2%, the mass proportion of the second additive is 0.5%, the mass proportion of the lithium salt additive is 1%, the mass ratio of the linear carbonate to the cyclic carbonate in the organic solvent is 60:40, and the lithium salt concentration is 1 mol / L.
[0051] The first additive is 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine, and the second additive is 2,2,3,3-tetrafluoropropyl trifluoromethanesulfonate;
[0052] The lithium salt is lithium hexafluorophosphate LiPF6;
[0053] The lithium salt additive is bis(fluorosulfonyl)imide lithium salt LiFSI;
[0054] The linear carbonates are dimethyl carbonate DMC and diethyl carbonate DEC, and the cyclic carbonates are propylene carbonate PC and fluoroethylene carbonate FEC (DMC:DEC:PC:FEC=20:40:20:20);
[0055] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0056] 2. Preparation of positive electrode
[0057] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.
[0058] 3. Preparation of negative electrode sheet
[0059] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0060] 4. Selection of isolation film
[0061] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0062] 5. Preparation of Lithium-ion Batteries
[0063] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0064] Example 3
[0065] 1. Preparation of Electrolyte
[0066] The mass proportion of the first additive in the electrolyte is 3%, the mass proportion of the second additive is 2%, the mass proportion of the lithium salt additive is 1%, the mass ratio of the linear carbonate to the cyclic carbonate in the organic solvent is 80:20, and the lithium salt concentration is 1.5 mol / L.
[0067] Wherein, the first additive is 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine, and the second additive is 2,2-difluoroethyl trifluoromethanesulfonate;
[0068] The lithium salt is lithium hexafluorophosphate LiPF6;
[0069] The lithium salt additive is lithium difluorophosphate LiPO2F2;
[0070] The linear carbonates are diethyl carbonate DEC and methylpropyl carbonate MPC, and the cyclic carbonates are ethylene carbonate EC and propylene carbonate PC (DEC: MPC: EC: PC = 60: 20: 10: 10);
[0071] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0072] 2. Preparation of positive electrode
[0073] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.
[0074] 3. Preparation of negative electrode sheet
[0075] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0076] 4. Selection of isolation film
[0077] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0078] 5. Preparation of Lithium-ion Batteries
[0079] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0080] Example 4
[0081] 1. Preparation of Electrolyte
[0082] The mass proportion of the first additive in the electrolyte is 2.5%, the mass proportion of the second additive is 2%, the mass proportion of the lithium salt additive is 1%, the mass ratio of the linear carbonate to the cyclic carbonate in the organic solvent is 80:20, and the lithium salt concentration is 1.3 mol / L.
[0083] The first additive is 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine, and the second additive is hexafluoroisopropyl trifluoromethanesulfonate;
[0084] The lithium salt is lithium hexafluorophosphate LiPF6;
[0085] The lithium salt additive is lithium bis(trifluoromethanesulfonyl)imide LiTFSI;
[0086] The linear carbonates are diethyl carbonate DEC and methylpropyl carbonate MPC, and the cyclic carbonates are fluoroethylene carbonate FEC and propylene carbonate PC (DEC: MPC: EC: FEC = 50: 30: 10: 10);
[0087] The linear carbonate and the cyclic carbonate are stirred and mixed evenly to obtain a first mixture; the lithium salt is added to the first mixture and stirred and mixed evenly to obtain a second mixture; the first additive and the second additive are added to the second mixture and stirred and mixed evenly to obtain an electrolyte.
[0088] 2. Preparation of positive electrode
[0089] The ternary material NCM (LiNi 0.9 Co 0.05 Mn 0.05 O2) positive electrode active material, binder PVDF (polyvinylidene fluoride), conductive agent SP (conductive carbon black Super-P) are mixed and stirred evenly in a mass ratio of 96:1.8:2.2 to obtain positive electrode slurry, and then the positive electrode slurry is coated on aluminum foil through a coating process, and the positive electrode sheet is obtained after drying and cold pressing processes.
[0090] 3. Preparation of negative electrode sheet
[0091] Silicon-carbon negative electrode material, conductive agent SP (conductive carbon black Super-P), SWCNT (single-walled carbon nanotube) and binder PAA (polyacrylic acid) are mixed and stirred in a mass ratio of 83.5:8:0.5:8 to obtain negative electrode slurry, and the solid content is controlled at 30%. The negative electrode slurry is then coated on the current collector on the copper foil through a coating process, and the negative electrode sheet is obtained after vacuum drying and cold pressing processes.
[0092] 4. Selection of isolation film
[0093] Polyethylene (PE) + ceramics are selected as the isolation membrane for lithium-ion batteries.
[0094] 5. Preparation of Lithium-ion Batteries
[0095] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then a bare battery cell is obtained; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a soft-pack lithium-ion battery is obtained.
[0096] Example 5
[0097] The difference between this embodiment and embodiment 1 is that a third additive 1,3-propane sultone PS is further included, and the mass proportion of the third additive in the electrolyte is 1%; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0098] Example 6
[0099] The difference between this embodiment and embodiment 1 is that a third additive, vinyl sulfate DTD, is further included, and the mass proportion of the third additive in the electrolyte is 3%; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0100] Example 7
[0101] The difference between this embodiment and embodiment 1 is that the mass proportion of the first additive in the electrolyte is 4%, and the mass proportion of the second additive in the electrolyte is 0.1%; the remaining steps and parameter settings are consistent with embodiment 1.
[0102] Example 8
[0103] The difference between this embodiment and embodiment 1 is that the mass proportion of the first additive in the electrolyte is 0.5%, and the mass proportion of the second additive in the electrolyte is 3%; the remaining steps and parameter settings are consistent with embodiment 1.
[0104] Example 9
[0105] The difference between this embodiment and embodiment 1 is that an equal weight of propyl acetate EP is used to replace the linear carbonate in embodiment 1; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0106] Example 10
[0107] The difference between this embodiment and embodiment 1 is that the mass ratio of linear carbonate to cyclic carbonate is 20:80; the remaining steps and parameter settings are consistent with those in embodiment 1.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 1 is that the electrolyte does not contain the first additive and the second additive; the remaining steps and parameter settings are consistent with Example 1.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 1 is that the electrolyte contains only the first additive; the remaining steps and parameter settings are consistent with those of Example 1.
[0112] Comparative Example 3
[0113] The difference between this comparative example and Example 1 is that the electrolyte contains only the second additive; the remaining steps and parameter settings are consistent with those of Example 1.
[0114] Comparative Example 4
[0115] The difference between this comparative example and Example 1 is that an equal weight of 5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-1H-indazole is used to replace the first additive 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine in Example 1; the remaining steps and parameter settings are consistent with Example 1.
[0116] Test Method
[0117] 1. The first coulombic efficiency test of lithium battery
[0118] The lithium batteries in the above embodiments and comparative examples were subjected to the first coulombic efficiency test. The specific test steps were as follows: at 25°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 0.33C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 0.33C, and allowed to stand for 10 minutes. The first coulombic efficiency of the lithium ion battery was calculated.
[0119] First coulombic efficiency (%) = total capacity of the lithium-ion battery discharged at 0.33C for the first time / total capacity of the lithium-ion battery charged at 0.33C for the first time × 100%.
[0120] 2. Lithium battery cycle performance test
[0121] 2.1. Lithium battery capacity retention rate during normal temperature cycling
[0122] The lithium batteries in the above embodiments and comparative examples were tested for capacity retention rate under normal temperature cycles. The specific test steps were as follows: at 25°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 1C, and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The lithium ion battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate of the lithium ion battery after 1000 cycles of charge and discharge at 1C / 1C was calculated.
[0123] 2.2. Lithium battery high temperature cycle capacity retention rate
[0124] The lithium batteries in the above embodiments and comparative examples were tested for capacity retention rate under normal temperature cycles. The specific test steps were as follows: at 45°C, the lithium ion battery was charged to 4.2V at a constant current and constant voltage rate of 1C, with a cut-off current of 0.05C, and allowed to stand for 10 minutes. Then, the lithium ion battery was discharged to 2.5V at a constant current rate of 1C, and allowed to stand for 10 minutes. This was considered one charge and discharge cycle. The lithium ion battery was charged and discharged for 1000 cycles according to the above method, and the capacity retention rate of the lithium ion battery after 1000 cycles of charge and discharge at 1C / 1C was calculated.
[0125] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0126] 3. Rate performance test
[0127] The lithium batteries of the above embodiments and comparative examples were subjected to rate performance tests, and the specific test steps were as follows: at 25°C, the lithium ion battery was discharged at a constant current rate of 1C to 2.5V, and allowed to stand for 10 minutes, and then the lithium ion battery was charged at a constant current and constant voltage rate of 6C to 4.2V, with a cut-off current of 0.05C, and allowed to stand for 10 minutes, and the constant current charging capacity Q1 and the constant current and constant voltage charging total capacity Q2 of the lithium ion battery were recorded, and the 6C rate charging constant current charging ratio was calculated according to the following formula: 6C rate charging constant current charging ratio = constant current charging capacity Q1 / constant current and constant voltage charging total capacity Q2 × 100%.
[0128] 4. Safety performance test
[0129] The lithium batteries of the above embodiments and comparative examples are subjected to thermal runaway tests, and the specific test steps are as follows: the test sample is heated from room temperature to 45±2°C in the chamber, and after being left for 90 minutes, the change in the temperature rise rate of the battery is detected. If the temperature rise exceeds 0.2°C within 10 minutes (i.e., SHR>0.02°C / min), it is considered that a self-exothermic reaction occurs inside the battery, and an adiabatic environment is maintained until the battery undergoes thermal runaway; if the temperature rise does not exceed 0.2°C within 10 minutes (i.e., SHR≤0.02°C / min), continue to the next step temperature rise test; each temperature step is 5°C, and the steps are repeated on each step. The ARC test temperature range is 45-300°C, the starting temperature of self-heat generation is T1 (temperature rise rate SHR>0.02°C / min), and the starting temperature of thermal runaway is T2 (temperature rise rate SHR>1°C / min).
[0130] Table 1
[0131]
[0132] In combination with Example 1, Comparative Examples 1-4 and Table 1, it can be seen that the present application, by using 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine in combination with fluorinated sulfonate additives, can not only appropriately increase the free lithium content in the electrolyte and improve the ionic conductivity of the electrolyte, but also promote the formation of stable LiF interface film and Li2S interface film at the recharge interface, which are helpful to improve the rate performance and first-efficiency performance of the lithium battery; and, the boron element can cooperate with the sulfonic acid group to improve the film formation stability of the electrode surface and improve the cycle capacity retention rate of the lithium battery, while the fluorine element and the sulfonic acid group can improve the flame retardant effect of the electrolyte, help to increase the self-heating starting temperature of the lithium battery, and further improve the fast charging safety of the lithium battery.
[0133] In combination with Examples 1-4 and Table 1, it can be seen that in the present application, by introducing a lithium salt additive into the electrolyte, the quality of the interface film on the electrode surface can be improved, the film layer structure can be refined, and the interface film on the electrode surface can be made more uniform and dense, which helps to improve the cycle capacity retention rate and rate performance of the lithium battery.
[0134] In combination with Example 1, Examples 5-6 and Table 1, it can be seen that the present application can further improve the stability of the electrode / electrolyte interface, improve the cycle capacity retention rate of the lithium battery, improve the high temperature cycle performance of the lithium battery, and increase the starting temperature of the self-heating of the lithium battery by adding a third additive in combination with 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine and a fluorinated sulfonate additive ester into the electrolyte.
[0135] In combination with Example 1, Examples 7-8 and Table 1, it can be seen that when the content of 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine is too high and the content of the fluorinated sulfonate additive is too low, the free lithium content in the electrolyte may be too high and cannot be consumed to form a LiF interface film, resulting in a decrease in the stability of the electrolyte, especially the cycle capacity retention rate and the self-heating starting temperature of the lithium battery, which have a significant downward trend compared to the lithium battery in Example 1; when 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine is too high and the content of the fluorinated sulfonate additive is too low, the free lithium content in the electrolyte may be too high and cannot be consumed to form a LiF interface film, resulting in a decrease in the stability of the electrolyte, especially the cycle capacity retention rate and the self-heating starting temperature of the lithium battery, which have a significant downward trend compared to the lithium battery in Example 1; When the content of 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine and fluorinated sulfonate additives is too low and the content of fluorinated sulfonate additives is too high, the absorption effect of the dioxaborolanyl group on HF in the electrolyte is not significant, and the generation of free lithium in the electrolyte cannot be promoted, resulting in a decrease in the stability of the interface film at the negative electrode, and a significant decrease in the rate performance and cycle capacity retention rate of the lithium battery; the present application controls the mass proportion of 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine and fluorinated sulfonate additives in the electrolyte to meet the above range, which can help improve the rate performance, cycle performance and safety performance of the lithium battery.
[0136] In combination with Example 1, Examples 9-10 and Table 1, it can be seen that the present application uses linear carbonates and cyclic carbonates with the above-mentioned ratio as organic solvents. On the one hand, it helps to improve the stability of the electrolyte system and the stability of the first additive and the second additive in the electrolyte so that the two can work together to achieve the desired effect. On the other hand, it can adjust the appropriate electrolyte viscosity and generate an SEI film on the surface of the negative electrode active material, which helps to improve the rate performance and cycle performance of the lithium battery.
[0137] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.
Claims
1. An electrolyte, characterized in that: The invention comprises a first additive and a second additive, wherein the first additive comprises 2-(difluoromethoxy)-5-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)pyridine, and the second additive comprises a fluorinated sulfonate additive.
2. The electrolyte according to claim 1, wherein the fluorinated sulfonate additive comprises at least one of 2,2,3,3,3-pentafluoropropyl trifluoromethanesulfonate, 2,2,3,3-tetrafluoropropyl trifluoromethanesulfonate, 2,2-difluoroethyl trifluoromethanesulfonate, and hexafluoroisopropyl trifluoromethanesulfonate.
3. The electrolyte according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 1%-3%, and / or the mass proportion of the second additive in the electrolyte is 0.5%-2.5%.
4. The electrolyte according to any one of claims 1 to 3, characterized in that: It also includes an organic solvent, a lithium salt, a lithium salt additive and a third additive.
5. The electrolyte according to claim 4, characterized in that: The third additive includes at least one of 1,3-propane sultone, vinyl sulfate, and 1,3-propylene sultone; The mass proportion of the third additive in the electrolyte is 1%-3%.
6. The electrolyte according to claim 4, characterized in that: The lithium salt additive includes at least one of bis(fluorosulfonyl)imide lithium salt, lithium tetrafluoroborate, lithium difluorophosphate and bis(trifluoromethanesulfonyl)imide lithium; The lithium salt additive accounts for 0.1%-1% by mass in the electrolyte.
7. The electrolyte according to claim 4, characterized in that: The organic solvent includes at least one of a linear carbonate and a cyclic carbonate.
8. The electrolyte according to claim 7, characterized in that: The linear carbonate includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; the cyclic carbonate includes at least one of ethylene carbonate, fluoroethylene carbonate and propylene carbonate.
9. The electrolyte according to claim 7, characterized in that: The mass ratio of the linear carbonate to the cyclic carbonate is 60-80:20-40.
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Electrolyte suitable for silicon-carbon negative electrode and lithium ion battery
CN111834671A
Electrolytic solution and electrochemical device comprising same
CN113130994A
Preparation method of mannitol-cyclic fluoride acid ester compound
CN117143154A
Boron-containing sulfonic ester compound, additive agent for nonaqueous electrolytic solution, nonaqueous electrolytic solution, and electric power storage device
JP2014194870A